PENGARUH HARGA, LOKASI DAN INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN PADA WARUNG STEAK JALAN T. AMIR HAMZAH MEDAN - Shamir Hasyim Syarif (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
This research was conducted to determine the influence of price, location and product innovation on consumer satisfaction at Waroeng Steak and Shake Jalan T. Amir Hamzah Medan. The population was 4200 people with a sample of 98 respondents. This research uses quantitative data and multiple linear regression methods. The test results show that price has a negative but not significant effect on consumer satisfaction. Location variables have a significant effect on consumer satisfaction. The Product Innovation variable has a significant effect on Consumer Satisfaction